Reciprocal Expression of Two Candidate Di-Iron Enzymes Affecting Photosystem I and Light-Harvesting Complex Accumulation - Moseley, Jeffrey L. (American Society of Plant Biologists, 2002)
Crd1 (Copper response defect 1), which is required for the maintenance of photosystem I and its associated light-harvesting complexes in copper-deficient (−Cu) and oxygen-deficient (−O(2)) Chlamydomonas reinhardtii cells, is localized to the thylakoid membrane. A related protein, Cth1 (Copper target homolog 1), is shown to have a similar but not identical function by genetic suppressor analysis of gain-of-function sct1 (suppressor of copper target 1) strains that are transposon-containing alleles at CTH1. The pattern of Crd1 versus Cth1 accumulation is reciprocal; Crd1 abundance is increased in −Cu or −O(2) cells, whereas Cth1 accumulates in copper-sufficient (+Cu), oxygenated cells. This expression pattern is determined by a single trans-acting regulatory locus, CRR1 (COPPER RESPONSE REGULATOR 1), which activates transcription in −Cu cells. In +Cu cells, a 2.1-kb Cth1 mRNA is produced and translated, whereas Crd1 is transcribed only at basal levels, leading to Cth1 accumulation in +Cu cells. In −Cu cells, CRR1 function determines the activation of Crd1 expression and the production of an alternative 3.1-kb Cth1 mRNA that is extended at the 5′ end relative to the 2.1-kb mRNA. Synthesis of the 3.1-kb mRNA, which encodes six small upstream open reading frames that possibly result in poor translation, blocks the downstream promoter through transcriptional occlusion. Fluorescence analysis of wild-type, crd1, and sct1 strains indicates that copper-responsive adjustment of the Cth1:Crd1 ratio results in modification of the interactions between photosystem I and associated light-harvesting complexes. The tightly coordinated CRR1-dependent regulation of isoenzymes Cth1 and Crd1 reinforces the notion that copper plays a specific role in the maintenance of chlorophyll proteins.